The Role of Tranformational Leadership in Enhancing an Inclusive Organizational Culture at PT Indofood Sukses Makmur TBK Bandung: a Study on Workforce Diversity Program Implementation - Hendriawanto Hendriawanto; Gurawan Dayona Ismail; Mochammad Mukti Ali; Nunung Ayu Sofiaty; Yoyo Sudaryo (Green Publisher Indonesia, 2025)
This study analyzes the impact of transformational leadership and employee performance on an inclusive organizational culture at PT Indofood Sukses Makmur Tbk, Bandung. Using path analysis, the results reveal that transformational leadership significantly enhances an inclusive culture, supported by the positive contribution of employee performance. The workforce diversity program plays a key role in promoting diversity and inclusion. Recommendations include leadership training, strengthening diversity programs, and implementing performance evaluations centered on inclusion.